Teach me everyday French. Volume 2, Celebrating the seasons [compact disc] - Mahoney, Judy (Teach me--., 2009)
Follow Marie her brother Peter and their dog Médor as they plant a garden, visit the zoo, picnic at the beach, celebrate the holidays and other events of the season. Presents an enjoyable approach to exploring new languages as it introduces common words, phrases and concepts to the beginning language learner through delightful songs and story.